Heat will kill you first : life and death on a scorched planet - Goodell, Jeff (New York [etc.] Little, Brown and Company, 2023)
The Heat Will Kill You First is about the extreme ways in which our planet is already changing. It is about why spring is coming a few weeks earlier and fall is coming a few weeks later and the impact that will have on everything from our food supply to disease outbreaks. It is about what will happen to our lives and our communities when typical summer days in Chicago or Boston go from 90°F to 110°F. A heatwave, Goodell explains, is a predatory event--one that culls out the most vulnerable people. But that is changing. As heatwaves become more intense and more common, they will become more democratic. As an award-winning journalist who has been at the forefront of environmental journalism for decades, Goodell's new book may be his most provocative yet, explaining how extreme heat will dramatically change the world as we know it
Keywords: Calentamiento global; Cambios climáticos